Influência de polimorfismos de genes KIR e de seus ligantes HLA na susceptibilidade ao dengue - Beltrame, Letícia Maria (2010)
Killer cell immunoglobulin-like receptor (KIR) genes encode activating and inhibitory molecules present on natural killer (NK) cells and have as binding human leukocyte antigen (HLA) class I molecules. The purpose of this study was to investigate the influence of KIR genes and their class I HLA ligands in susceptibility to dengue fever in a population from South Brazil through a case-control study. Ninety-five subjects with confirmed diagnoses of dengue participated in this study, along with a control group of 172 individuals, whose serologic tests for the detection of IgG antibodies against dengue were negative. HLA and KIR genotyping was performed by polymerase chain reaction with sequence-specific oligonucleotides probes (PCR-SSOP) and polymerase chain reaction with sequence-specific primers (PCR-SSP) techniques, respectively. Data analysis showed significant differences for KIR2DS1 (55.8% vs 40.7%, P = 0.02), KIR2DS3 (47.4% vs 33.7%, P = 0.03), KIR2DS5 (50.5% vs 36.0%, P = 0.02) and KIR2DL5 (77.9% vs 56.4%, P = 0.0007) genes. With regard to KIR-ligand pairs, positive associations with dengue were observed in KIR3DS1-Bw4 (38.9% vs 26.1%, P = 0.04), KIR2DL1-C2 (75.8% vs 62.2%, P = 0.03) and KIR2DS1-C2 (42.1% vs 25.6%, P = 0.0081) interactions, and a negative association in KIR2DL3-C1/C1 (16.8% vs 33.1%, P = 0.0066). The analysis of KIR haplotypes revealed a possible protective factor against dengue fever in individuals with the AA genotype. These results suggest the existence of genetic predisposition to dengue fever in the population from South Brazil.